2001
DOI: 10.1093/emboj/20.24.7074
|View full text |Cite
|
Sign up to set email alerts
|

A PEST-like element in FREQUENCY determines the length of the circadian period in Neurospora crassa

Abstract: FREQUENCY (FRQ) is a crucial element of the circadian clock in Neurospora crassa. In the course of a circadian day FRQ is successively phosphorylated and degraded. Here we report that two PEST-like elements in FRQ, PEST-1 and PEST-2, are phosphorylated in vitro by recombinant CK-1a and CK-1b, two newly identi®ed Neurospora homologs of casein kinase 1e. CK-1a is localized in the cytosol and the nuclei of Neurospora and it is in a complex with FRQ in vivo. Deletion of PEST-1 results in hypophosphorylation of FRQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
235
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(243 citation statements)
references
References 58 publications
8
235
0
Order By: Relevance
“…When protein synthesis was inhibited with cycloheximide, FRQ in complex with the FLAG FRH (followed by FLAG-IP) was degraded with a half-time of 3.5 h (Fig. 2c), which corresponds to the previously reported degradation kinetics of FRQ 6,23 . FRQ in complex with Walker A and DEAD box mutants of FLAG FRH was degraded significantly faster (Fig.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…When protein synthesis was inhibited with cycloheximide, FRQ in complex with the FLAG FRH (followed by FLAG-IP) was degraded with a half-time of 3.5 h (Fig. 2c), which corresponds to the previously reported degradation kinetics of FRQ 6,23 . FRQ in complex with Walker A and DEAD box mutants of FLAG FRH was degraded significantly faster (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Fourhundred micrograms of N. crassa and 100 mg of S. cerevisiae extract were analysed by SDS-PAGE and transferred to a nitrocellulose membrane (GE Healthcare; 0.45 mm, 10 Â 150 cm) in 150 mM glycine, 20 mM Tris, 20% (v/v) methanol and 0.08% (w/v) SDS at 200 mA for 2.5 h. The membrane was blocked with TBS and 5% milk (pH 7.4) before incubation with antibodies 6,29 . Antibodies against FRQ were used 1:20 diluted in 5% milk and CK1a antibodies at a dilution of 1:500 in 5% milk 6,23 . An FRH (1:350 in 5% milk) antibody was raised in rabbits against a peptide corresponding to amino-acid residues 2-18 (Pineda, Berlin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimate that ∼40%-50% of WC-1 is degraded through this process. Phosphorylation-dependent protein degradation has been demonstrated for FRQ in Neurospora, a critical process regulating the circadian clock (Liu et al 2000;Gorl et al 2001;Yang et al 2002Yang et al , 2004He et al 2003).…”
Section: Photoadaptation In Neurosporamentioning
confidence: 99%
“…Previous studies have demonstrated that phosphorylation of circadian clock proteins is an essential posttranscriptional mechanism in the regulation of circadian clocks (Dunlap 1999;Young and Kay 2001). Several kinases, including casein kinase I (CKI) and CKII, have been shown to phosphorylate and regulate the key clock components in eukaryotic systems Sugano et al 1999;Lowrey et al 2000;Gorl et al 2001;Yang et al 2002).FREQUENCY (FRQ), WHITE COLLAR-1 (WC-1), and WC-2 proteins are three key components in the Neurospora frq-wc-based circadian oscillator . In addition to being the circadian blue light photoreceptor (Froehlich et al 2002;He et al 2002), in the dark, WC-1 forms a heterodimeric complex with WC-2 through their PAS domains and activate frq transcription by binding its promoter (Crosthwaite et al 1997;Talora et al 1999;Cheng et al 2001bCheng et al , 2002Cheng et al , 2003Froehlich et al 2003).…”
mentioning
confidence: 99%